"A Clock So True": The Chronometry of Virtue in Donne's "Obsequyes vpon the Lord Harrington". (February 2014) - DiPasquale, Theresa M.
<x xml:space="preserve">Abstract</x> The most compelling portrayal of timekeeping technology in an English poem of the early seventeenth century is a long and complicated passage from John Donne's 1614 poem "Obsequyes vpon the Lord Harrington the last that dyed." In this passage, Donne deploys clock and sundial images to critique the values of the religio‐political faction with which the deceased Lord Harington was associated, a group of courtiers and scholars strongly invested in the development of new technologies. Comparing human beings to timepieces in a conceit that plays upon the traditional iconography of Temperance, Donne challenges technological progressivism, promoting in its place a skeptical chronometry of virtue. Donne's conceit poses interpretive challenges that force readers to think analytically and critically about how technology—and in particular the technology of time‐measurement—is related to human goodness and well‐being. [T. M. D.]